Cross-border tourism in Indonesia: trends, opportunities, challenges, and research agenda - Salouw, Elvis; Setiawan, Bakti; Sarwadi , Ahmad (International Journal of Applied Sciences in Tourism and Events, 2023)
The discourse on cross-border tourism (C-BT) has become an interesting topic for researchers in the last few decades. Indonesia, as an archipelagic country, has very promising C-BT potential. However, there is not much literature on C-BT in Indonesia. Therefore, this study aims to describe qualitatively the development of tourism research in Indonesia related to C-BT. In addition, this study also seeks to identify articles, chapter books, and conference papers related to C-BT in Indonesia and then analyze them to produce a systematic literature review and draw theoretical implications. The method used in this study is a systematic literature review on C-BT in Indonesia. The databases used in this research are Scopus, Web of Science, and Google Scholar. The data collection in this study using PoP software, organizing data using Mendeley software, and analyzing data using NVIVO software. The study results show that research trends on cross-border tourism in Indonesia have increased in the last decade. In addition, opportunities for developing cross-border tourism in Indonesia are still open. On the other hand, the challenges faced by Indonesia in the development of cross-border tourism are dominated by governance that has not been maximized, which includes unresolved legal issues, lack of management of natural resources, communication, criminal & drug Smuggling, lack of border control, regulation, physical border arrangement, and lack of promotions and marketing